Identification of immunodominant HIV-1 epitopes presented by 2 HLA-C*12:02, a protective allele, using an immunopeptidomics 3 approach - Chikata, T; Paes, W; Akahoshi, T; Partridge, T; Murakoshi, H; Gatanaga, H; Ternette, N; Oka, S; Borrow, P; Takiguchi, M (American Society for Microbiology, 2019)
Despite the fact that cell-surface expression of HLA-C on both uninfected and HIV-infected cells is lower than that of HLA-A and -B, increasing evidence suggests an important role for HLA-C and HLA-C-restricted CD8 + T cell responses in determining the efficiency of viral control in HIV-1-infected individuals. Nonetheless, HLA-C-restricted T cell responses are much less well-studied than HLA-A/B-restricted ones, and relatively few optimal HIV-1 CD8 + T cell epitopes restricted by HLA-C alleles have been defined. Recent improvements in the sensitivity of mass spectrometry (MS)-based approaches for profiling the immunopeptidome present an opportunity for epitope discovery on a large scale. Here, we employed a mass spectrometry (MS)-based immunopeptidomic strategy to characterize HIV-1 peptides presented by a protective allele, HLA-C*12:02. We identified a total of 10,799 unique 8-12-mer peptides, including 15 HIV-1 peptides. The latter included 2 previously-reported immunodominant HIV-1 epitopes; and analysis of T cell responses to the other HIV-1 peptides detected revealed an additional immunodominant epitope. These findings illustrate the utility of MS-based approaches for epitope definition, and emphasize the capacity of HLA-C to present immunodominant T cell epitopes in HIV-infected individuals, indicating the importance of further evaluation of HLA-C-restricted responses to identify novel targets for HIV-1 prophylactic and therapeutic strategies. IMPORTANCE Mass spectrometry (MS)-based approaches are increasingly being employed for large-scale identification of HLA-bound peptides derived from pathogens, but only very limited profiling of the HIV-1 immunopeptidome has been conducted to date. Notably, a growing body of evidence has recently begun to indicate a protective role for HLA-C in HIV-1 infection, which may suggest that despite the fact that levels of HLA-C expression on both uninfected and HIV-1-infected cells are lower than those of HLA-A/B, HLA-C still presents epitopes to CD8 + T cells effectively. To explore this, we analyzed HLA-C*12:02-restricted HIV-1 peptides presented on HIV-1-infected cells expressing only HLA-C*12:02 (a protective allele) using LC-MS/MS. We identified a number of novel HLA-C*12:02-bound HIV-1 peptides, and showed that although the majority of them did not elicit T cell responses during natural infection in a Japanese cohort, they included three immunodominant epitopes, emphasizing the contribution of HLA-C to epitope presentation on HIV-infected cells.